2018
DOI: 10.1080/14653125.2018.1528746
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of rate of tooth movement and pain perception during accelerated tooth movement associated with conventional fixed appliances with micro-osteoperforations – a randomised controlled trial

Abstract: Objectives To investigate the influence of micro-osteoperforation (MOP) on rate of orthodontic tooth movement and pain perception with fixed appliances. Design 2 arm parallel randomized controlled trial with an allocation ratio of 1:1. Setting The outpatient department of a dental college. Participants 105 patients were screened, out of which 60 met the inclusion criteria and consented to participate; consisting of 33 females and 27 males requiring en-masse retraction following first premolar extractions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
104
0
12

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(118 citation statements)
references
References 36 publications
2
104
0
12
Order By: Relevance
“…Five studies [ 12 , 13 , 19 , 20 , 25 ] using the Excellerator instrument (Propel Orthodontics—Ossining, NY, USA) evaluated the effects of MOPs on the rate of tooth movement in orthodontic retraction compared to a control group without MOPs; also, seven RCTs [ 14 , 15 , 18 , 26 29 ] using other mini-screws performed the same evaluation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five studies [ 12 , 13 , 19 , 20 , 25 ] using the Excellerator instrument (Propel Orthodontics—Ossining, NY, USA) evaluated the effects of MOPs on the rate of tooth movement in orthodontic retraction compared to a control group without MOPs; also, seven RCTs [ 14 , 15 , 18 , 26 29 ] using other mini-screws performed the same evaluation.…”
Section: Resultsmentioning
confidence: 99%
“…Among eight studies which analyzed the pain associated with the interventions [ 12 15 , 20 , 25 , 28 , 29 ], one evaluated the impact on the daily routine of patients [ 14 ] and three studies evaluated the presence of root resorption [ 14 , 15 , 28 ]. None used the Propel system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple MOP procedures were performed in various studies to achieve this continued effect of cytokine release after giving MOPs, which showed a constant influence for a month on average. 3,9,17,31 Cramer et al 3 in their split-mouth animal study, however, demonstrated the application of eight MOPs at a depth of 7 mm on seven mature male beagle dogs in the jaw side randomly selected through computerized random number generation for the allocation of experimental and control sides. Contrary to the significant results in many studies, 14,17,28,29 there was not an increase in tooth movement rates due to MOPs.…”
Section: Micro-osteoperforations: Literature Searchmentioning
confidence: 99%
“…After an additional overall quality-of-evidence appraisal across all outcomes, our conclusion that single application micro-osteoperforations have no acceleration effect when observed over a short observation period, was based on only 2 studies 10,11 and the overall quality of the evidence was low. In essence, there is insufficient high-quality evidence to support that micro-osteoperforation is or is not effective for accelerating tooth movement.…”
mentioning
confidence: 95%